An investigation of the programs and equipment used by caregivers and day mothers for the age group 0-36 months in Limpopo Province, South Africa - Grey, Margaretha J. (My University, 2008)
ABSTRACT This study investigated the quality of care provided to children between 0 and 36 months in Limpopo Province. A non-experimental, quantitative, cross sectional descriptive design was used. The researcher developed two research instruments: • a questionnaire which collected information on registration, training, services provided stimulation programs, referral and equipment. • an observation sheet which recorded information on the premises, the staff, equipment and office, toys, outdoor play area, sleeping and dining areas. 111 subjects participated in the study- 19 day mothers in urban areas and 92 caregivers in more rural areas. Descriptive statistics were used to summarize the data in the questionnaire and the mean values for the two samples from the observation were compared using a t test. Results suggest that the quality of care provided by both day mothers and caregivers is below the accepted overall mean of 3 for all variables examined except day mother’s premises. Caregivers at care centres were better trained and offered more stimulation programmes than day mothers. They also scored better than day mothers with respect to staff and equipment with toys and dining areas being significantly better. Day mothers scored marginally higher than caregivers with respect to outdoor play and sleeping areas.
Keywords: programs; equipment; development; caregivers; day mothers